2005
DOI: 10.2169/internalmedicine.44.706
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Gouty Arthritis in Patients with End-stage Renal Disease in Japan

Abstract: Objective The purpose of this study was to investigate gouty arthritis in Japanese patients with end-stage renal disease (ESRD).Methods Questionnaires plus patient interviews and reviews of medical records were used to investigate gouty arthritis in 493 Japanese patients with ESRD receiving maintenance dialysis.Results The frequency of gouty arthritis was 4.1% for female patients and 15.4% for male patients greater than 2 years before the start of dialysis, and 0.6% for female patients and 7.7% for male patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 18 publications
(19 reference statements)
3
35
0
2
Order By: Relevance
“…Since febuxostat has a high binding affinity (over 98%) to plasma proteins such as albumin, it is difficult to dialyze by the kidney or a dialysis membrane [10] . The frequency of gout arthritis in patients receiving maintenance dialysis was previously shown to be lower than that in the general population [28] . However, hyperuricemia is a risk factor for cardiovascular diseases [3,4] and should be treated in patients receiving dialysis.…”
Section: Discussionmentioning
confidence: 94%
“…Since febuxostat has a high binding affinity (over 98%) to plasma proteins such as albumin, it is difficult to dialyze by the kidney or a dialysis membrane [10] . The frequency of gout arthritis in patients receiving maintenance dialysis was previously shown to be lower than that in the general population [28] . However, hyperuricemia is a risk factor for cardiovascular diseases [3,4] and should be treated in patients receiving dialysis.…”
Section: Discussionmentioning
confidence: 94%
“…These results contrast with previous smaller and single-center studies that found an infrequent rate of gout in dialysis patients. 1,2 The reasons for these disparities are not clear but may be related to the larger number of patients sampled or differences in lifestyle/diet. It is also likely that a significant number of patients with ESRD had a predialysis episode of gout that could not be identified because of the inherent limitations of an observational study.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The available research is limited by small sample sizes. The incidence of gout in dialysis patients is believed to be rare.…”
mentioning
confidence: 99%
See 2 more Smart Citations